REPREZENTAREA MODELELOR SUCCESIVE DE ELEVAŢIE ÎN RELAŢIE CU PROFILELE STRATIGRAFICE PE FONDUL DESFĂŞURĂRII SĂPĂTURILOR ARHEOLOGICE PREVENTIVE, PROPRIETATEA COLDA, AŞEZAREA LUMEA NOUĂ, ALBA IULIA (PANGEEA, 2025)
Representation of successive elevation models in relation with the stratigraphic profiles to the archaeological excavations in Colda property, placement Lumea Nouă, Alba Iulia. An overview of all elements measured (by default the past researched area) is offered by 3D representations of land and excavation, as appropriate. Current versions of GIS offers users a variety of user-friendly tools that do not require lengthy training. However, satisfactory results, it is necessary to tighten the working methods by applying the corresponding parameters.